End Cap Effect on Solution-Processable Deep Blue Lasing Materials with Low-Amplified Spontaneous Emission Thresholds - Sugai, Yoshiki; Rahane, Vijay P; Gale, Innes; Verdi, Carla; Ireland, Alexander R; Canola, Sofia; McGregor, Sarah K M; Moore, Evan G; Jain, Nidhi; Namdas, Ebinazar B; Lo, Shih-Chun (ACS applied materials & interfaces, 2024)
Organic lasers have attracted increasing attention owing to their superior characteristics such as lightweight, low-cost manufacturing, high mechanical flexibility, and high emission-wavelength tunability. Recent breakthroughs include electrically pumped organic laser diodes and an electrically driven organic laser, integrated with an organic light-emitting diode pumping. However, the availability of efficient deep blue organic laser chromophores remains limited. In this study, we develop two novel rigid oligophenylenes, end-capped with carbazole and phenylcarbazole groups, to demonstrate exceptional optical and amplified spontaneous emission (ASE) properties. These oligophenylenes are not only solution processable but also exhibit remarkably high solution photoluminescence quantum yields (PLQYs) of 90% and high radiative rates of 1.35 × 109 s-1 in the deep blue range. Our theoretical calculations confirm that the carbazole and phenylcarbazole end groups play a pivotal role in enhancing the optical transitions of the oligophenylene laser chromophores, thereby elevating their emission oscillator strengths. Remarkably, these materials demonstrate low solid-state ASE threshold values of 1.0 and 1.5 μJ/cm2 (at 431 and 418 nm, respectively). To the best of our knowledge, these ASE thresholds represent the lowest reported at these specific ASE wavelengths in the literature, regardless of whether they are solution-processed or thermally evaporated films. Furthermore, they exhibit excellent thermal and photostability, low triplet quantum yields, as well as negligible overlap of excited-state absorption within the ASE emission region, making them excellent candidates for a new class of deep blue materials for organic lasers. By integrating insights from theoretical calculations and experimental validation, our study provides a comprehensive understanding of the design principles behind these high-performing organic laser chromophores, paving the way for the development of advanced organic lasers with enhanced performance characteristics.
Keywords: deep blue lasing materials; radiative decay rate; excited-state absorption; carbazole and phenylcarbazole end-caps; amplified spontaneous emission